Reproductive Behavior and Parental Role of Giant Gourami (Osphronemus goramy Lacepède, 1801) - Junior, Timothy Irsyad; Hardaningsih, Ignatius; Bimasuci, Harya; Sari, Dini Wahyu Kartika (Journal of Tropical Biodiversity and Biotechnology, 2024)
The giant gourami (Osphronemus goramy Lacepede, 1801), a popular aquaculture species in Southeast Asia, exhibits unique cooperative biparental care behaviour. To support captive breeding efforts, this study aimed to visually document the reproductive activity of giant gourami, elucidate each stage in detail, and provide insights into the distinct parenting roles of males and females. Underwater cameras were used to observe a breeding pair of gourami in a pond for five days, conducted three times with different pairs during different spawning periods. The male and female contributions to nest building were quantitatively analysed using the T-test, while their parental care involvement was qualitatively assessed and statistically analysed using the Mann-Whitney U test. The results revealed three main phases of giant gourami reproduction: pre-spawning (including adaptation, nest building, and courtship), spawning and fertilisation, and post-spawning with parental care. Our observation confirmed the biparental tendency, with males being more involved in pre-spawning activities and females taking on a prominent role in post-spawning care. In conclusion, males focused on mating preparations and courtship, while females invested more in parental care.